FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN PEMBIAYAAN BERBASIS BAGI HASIL PADA BANK SYARIAH MANDIRI INDONESIA PERIODE 2003-2015 - Novia Nurbiaty; Tri Sukirno Putro; Anthony Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to find out how to the influence of Non Performing Finance, equivalent rate of profit sharing and third parties fund towards profit and loss sharing financing at Bank Syariah Mandiri Indonesia. This research uses secondary data obtained from the financial statement published, that is official website Bank Syariah Mandiri Indonesia registered at Bank Indonesia from 2003 to 2015 time span. In this research that became the dependent variable is the profit and loss sharing financing. While being independent variables is the Non Performing Finance, equivalent rate of profit sharing and third parties fund. The analysis used in this research is the multiple linear regression analysis. Tests conducted on the hypothesis and the reliability of the data (assuming classical) using significant level of 5%. The results indicate the Non Performing Finance negative and no significant affect on profit and loss sharing financing as evidenced by the negative t value of -0,487 and a significant value 0,638 > 0,05. Equivalent rate of profit sharing is positive and no significant affect on profit and loss sharing financing as evidenced by the positive t value of 1,536 and significant value 0,159 > 0,05. Third parties fund is positive and significant affect on profit and loss sharing financing as evidenced by the positive t value of 9,806 and significant value 0,000 < 0,05.Keywords : Profit and Loss Sharing Financing, NPF, Equivalent Rate of Profit Sharing and Third Parties Fund